Road Test and Naturalistic Driving Performance in Healthy and Cognitively Impaired Older Adults: Does Environment Matter? - Davis, Jennifer D. (2012)
BACKGROUND/OBJECTIVES: The road test is regarded as the gold standard for determining driving competence in older adults, but it is unclear how well the road test relates to naturalistic driving. The study objective was to relate the standardized road test to video recordings of naturalistic driving in older adults with a range of cognitive impairment. DESIGN: Cross-sectional observational study. SETTING: Academic medical center memory disorders clinic. PARTICIPANTS: 103 older drivers (44 healthy and 59 with cognitive impairment) who passed a road test. MEASUREMENTS: Error rate and global ratings of safety (pass with and without recommendations, marginal with restrictions or training, or fail) made by a professional driving instructor. RESULTS: There was fair agreement between global ratings on the road test and naturalistic driving. More errors were detected in the naturalistic environment, but this did not impact global ratings. Error scores between settings were significantly correlated, and the types of errors made were similar. History of crashes corrected for miles driven per week was related to road test error scores, but not naturalistic driving error scores. Global cognition (MMSE) was correlated with both road test and naturalistic driving errors. In the healthy older adults, younger age was correlated with fewer errors on the road test and greater errors in naturalistic driving. CONCLUSION: Road test performance is a reasonable proxy for estimating fitness to drive in older individuals’ typical driving environments. The differences between performance assessed by these two methods, however, remain poorly understood and deserve further study.